1977
DOI: 10.1128/jvi.24.1.326-342.1977
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Synthesis in Cells Infected by Frog Virus 3. VII. Transcriptional and Post-Transcriptional Regulation of Virus Gene Expression

Abstract: We have used improved techniques for separating individual species of RNA and protein to study the mechanisms that control gene expression by frog virus 3, a eucaryotic DNA virus. Forty-seven species of viral RNA and 35 viral polypeptide species were resolved by polyacrylamide gel electrophoresis. The relative molar ratios of virus-specific polypeptides synthesized at various times after infection were determined by computer planimetry and were compared with the molar ratios of appropriate-sized viral RNAs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
47
2
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 36 publications
10
47
2
1
Order By: Relevance
“…6). It has been suggested that this protein comprises 40% of the virion (Kelly & Tinsley 1972; Willis et al. 1977; Black et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6). It has been suggested that this protein comprises 40% of the virion (Kelly & Tinsley 1972; Willis et al. 1977; Black et al.…”
Section: Resultsmentioning
confidence: 99%
“…One of the unifying features of this virus group is the presence of a major capsid protein (MCP) of approximately 50 kDa. This is the predominant polypeptide produced upon viral infection and can account for up to 45% of virion protein (Kelly & Tinsley 1972; Willis, Goorha, Miles & Granoff 1977; Black, Blair, Butcher, Capinera & Happ 1981). The MCP genes have been fully sequenced from the invertebrate iridoviruses, insect iridescent virus type 22 (IV22), Tipula iridescent virus (TIV), Chilo iridescent virus (CIV), Wiseana iridescent virus (WIV) and Costelytra zealandica iridescent virus (CzIV) (Cameron 1990; Tajbakhsh, Lee, Watson & Seligy 1990; Stohwasser, Raab, Schnitzler, Janssen & Darai 1993; Webby & Kalmakoff 1999), and the vertebrate iridoviruses, lymphocystis disease virus (LCDV)‐1 and FV3 (Schnitzler & Darai 1993; Mao, Tham, Gentry, Aubertin & Chinchar 1996).…”
Section: Introductionmentioning
confidence: 99%
“…or late (i.e., synthesized at 2 h p.i. and thereafter), because once the synthesis of any viral RNA species had begun, its rate was maintained at the same or at a higher level (13).…”
mentioning
confidence: 99%
“…This drug, when incorporated into proteins in an essential site, renders such proteins nonfunctional without inhibiting protein synthesis in general (11). The addition of FPA at the beginning of infection had pleiotropic effects (13). Only the early RNAs were synthesized, even at 6 to 8 h p.i.…”
mentioning
confidence: 99%
See 1 more Smart Citation